Biochemical changes of fresh and preserved freshwater prawns (Macrobrachium rosenbergii) during storage - Abu Bakar, Fatimah; Salleh, Abu Bakar; Abdul Razak, Che Nyonya; Basri, Mahiran; Ching, Mai Keow; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2008)
Biochemical analysis was carried out for pH profiles, freshness in terms of K-values, amino acids profiles, total volatile bases (TVB), total volatile acids (TVA) and biogenic amines for fresh and preserved Macrobrachium rosenbergii. Results showed that pH profiles of Macrobrachium rosenbergii explain the inability of this parameter to be used to evaluate the quality of Macrobrachium rosenbergii. Thus changes in pH profiles of Macrobrachium rosenbergii should be combined with indicators such as total volatile acids and total volatile bases. Total volatile acids of the shrimps increased steadily in small amounts throughout the storage period. A rapid increase in TVB at 100C was detected due to the increase in total aerobic bacteria at elevated temperatures. The microbial activities caused the decrease in the amino acids arginine, lysine and histidine which correlated well with the increase in the corresponding biogenic amines such as putrescine, cadaverine and histamine respectively. Preservatives used in this study controlled the production of these biogenic amines without significantly altering the pH of preserved shrimp.